The role of online support groups for parents of adolescents with type 1 diabetes during the transition to adult diabetes services - Shepherd, Karen Louise (2021)
Paediatric type 1 diabetes is often referred to as a 'family disease' due to the importance of family interactions and parental supervision required to achieve optimal blood glucose levels and quality of life. The treatment regime for this chronic disease in children is complex and requires co-management by parents, many of whom experience psychosocial problems whilst undertaking this responsibility. Parents managing their child’s diabetes care need informational and emotional support that is not always adequately met by existing sources of support. With Internet access becoming increasingly ubiquitous, parents can search online for health information, advice and support, augmented by the use of diabetes online support groups. Previous research has identified potential benefits health-related online support groups can afford patients with chronic health conditions; addressing their information and support needs in a safe, non-judgemental environment with others in a similar situation, shown to empower individuals. However, little is known about the role of diabetes online support groups for parents of children with type 1 diabetes as they transition from paediatric to adult diabetes services during late adolescence; a particularly stressful event for some parents. The present thesis aimed to address this disparity by exploring parents of adolescent’s experiences of using diabetes online support groups during a period of change; investigating if group membership affects psychological well-being and if participation empowers parents. Using a mixed methods approach, three empirical studies were conducted. The first study used an online survey completed by 88 parents. This garnered information about parents’ experiences of using diabetes online support groups. It assessed the illness representations held about diabetes, along with reported levels of parental diabetes distress. Perceptions of empowering processes and outcomes within the diabetes online support groups were also investigated. For Study 2, qualitative one-to-one interviews were carried out with 13 parents who had previously completed the online survey, to gain a greater understanding of parents’ initial motivation to join a diabetes online support group, and what factors influence their continued participation. The final study was a thematic analysis of 945 messages posted on two UK diabetes online support groups to identify and examine the types of social support in group members’ communications. The combined results from the three studies indicate diabetes online support groups play an important role in providing informational and emotional support to parents of adolescents with type 1 diabetes. Furthermore, the availability and reciprocity of social support within diabetes online group were considered empowering by parents, with positive psychosocial benefits noted as being associated with group membership rather than dependant on the level of participation. Findings from this thesis also identified a disparity between mothers and fathers using diabetes online support groups, suggesting a more targeted approach should be considered for future research to investigate fathers’ perspectives and experiences. This thesis provides a deeper understanding of issues pertinent to the use of diabetes online support groups by parents of adolescents with type 1 diabetes. It provides a unique insight into the implications and potential benefits diabetes online support groups can have for the psychological well-being of parents for whom relinquishing control of their child’s diabetes management may be a determinant of increased anxiety, fear and diabetes distress.